The Observatory Health Report (Italian Journal of Public Health, 2008)
Background: The number of indicators aiming to provide a clear picture of healthcare needs and the qualityand efficiency of healthcare systems and services has proliferated in recent years. The activity of the NationalObservatory on Health Status in the Italian Regions is multidisciplinary, involving around 280 public healthcare experts, clinicians, demographers, epidemiologists, mathematicians, statisticians and economists whowith their different competencies, and scientific interests aim to improve the collective health of individualsand their conditions through the use of “core indicators”. The main outcome of the National Observatory onHealth Status in the Italian Regions is the “Osservasalute Report – a report on health status and the qualityof healthcare assistance in the Italian Regions”.Methods: The Report adopts a comparative analysis, methodology and internationally validated indicators.Results: The results of Observatory Report show it is necessary:• to improve the monitoring of primary health care services (where the chronic disease could be cared)through implementation of clinical path;• to improve in certain areas of hospital care such as caesarean deliveries, as well as the average length ofstay in the pre-intervention phase, etc.;• to try to be more focused on the patients/citizens in our health care services;• to practice more geographical interventions to reduce the North-South divide as well as reduce gender inequity.Conclusions: The health status of Italian people is good with positive results and outcomes, but in themeantime some further efforts should be done especially in the South that still has to improve the quality andthe organization of health care services. There are huge differences in accuracy and therefore usefulness ofthe reported data, both between diseases and between Regions.
Keywords: health status; health services; health reports